METASTATIC EPITHELIOID ANGIOSARCOMA MIMICKING CARCINOMA: CASE REPORT. (February 2015) - Welham, T.; Fadia, M.
Abstract : A 66-year-old man presented to his general practitioner with bilateral groin pain for the past 2 months. The CT scan revealed a 6.5 cm adrenal mass and multiple osteolytic bone and soft tissue metastases. Histology of right adrenal biopsy showed a cytokeratin positive poorly differentiated carcinoma. However, due to small amount of biopsy sample very limited immunostains were performed. Later on, the femoral reamings obtained showed a large-cell malignancy composed sheets of pleomorphic epitheliod cells with vesicular chromatin and prominent nucleoli. On immunohistochemistry, the tumour cells expressed AE1/AE3, CD31, CD34 and ERG. The ultrastructure examination showed Weibel-Palade bodies. Overall, on histomorphology and immunoprofile this was finally diagnosed as an epithelioid angiosarcoma. The patient was discharged home with a plan for treatment, but soon passed away. Epithelioid angiosarcomas are a rare variant of angiosarcoma, which is highly aggressive, and can mimic multiple other epithelioid malignancies. It often presents a diagnositic dilemma, as no obvious vasoformative channels are present. Furthermore, the cytokeratin expression characteristic of this tumour often leads to a misdiagnosis of metastatic carcinoma.